2023
DOI: 10.1177/01926365231158595
|View full text |Cite
|
Sign up to set email alerts
|

High School Principals’ Perceptions of Dual Enrollment Policy in Ohio and Texas

Abstract: Dual enrollment policies and programs, where students earn both high school and college credits, have been scaled up across the United States in the last two decades. In this mixed methods study, we survey high school principals in Ohio and Texas, two states with robust dual enrollment policies. The study addressed one broad research question: What are principals’ perceptions of dual enrollment access, participation, and governance? Findings revealed three main themes: (1) economic/credential student motivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…DC courses are college classes delivered to high-school students through partnerships between secondary schools and postsecondary institutions, most often community colleges [5] (Taylor et al , 2022). High-school students who take DC courses gain exposure to college curriculum and the opportunity to earn college credits, often at a discount (Hornbeck et al , 2023). A growing literature has shown that DC participation increases postsecondary enrollment and completion (An and Taylor, 2019; Blankenberger et al , 2017), and socializes students into college academics (Duncheon, 2020; Tobolowsky and Allen, 2016).…”
mentioning
confidence: 99%
“…DC courses are college classes delivered to high-school students through partnerships between secondary schools and postsecondary institutions, most often community colleges [5] (Taylor et al , 2022). High-school students who take DC courses gain exposure to college curriculum and the opportunity to earn college credits, often at a discount (Hornbeck et al , 2023). A growing literature has shown that DC participation increases postsecondary enrollment and completion (An and Taylor, 2019; Blankenberger et al , 2017), and socializes students into college academics (Duncheon, 2020; Tobolowsky and Allen, 2016).…”
mentioning
confidence: 99%